Genetic dissection of amino acid content in rice grain - Lu, Kaiyang; Li, Lanzhi; Zheng, Xingfei; Zhang, Zhihong; Mou, Tongmin; Hu, Zhongli (Journal of the science of food and agriculture, 2009)
BACKGROUND: Protein content and amino acid composition in rice are the most important components of rice nutrient quality. However, there have been few reports on the mapping of quantitative trait loci (QTLs) for the contents of protein and amino acids in rice grain and other crops (soybean, corn). In this study a population of 241 recombinant inbred lines (RILs) from a cross between Zhenshan 97 and Minghui 63 (the parents of the most widely grown hybrid rice in China) was constructed to detect the main effect and epistatic effect QTLs for amino acid content (AAC) as characterised by individual AACs, total essential AAC and total AAC.RESULTS: Using a linkage map covering a total of 1796 centimorgan (cM) based on 221 molecular marker loci, a total of 12 QTLs were identified for ten traits mapped on chromosomes 1, 4, 6, 7 and 11. The QTL cluster (flanked by C904, R2632 and C39) on chromosome 1 was associated with the content of eight amino acids. The phenotypic variation explained by individual QTLs ranged from 3.4 to 48.8%. Eighty-one digenic interactions were resolved that involved 143 loci distributed on all 12 chromosomes. The amount of variation explained by main effect QTLs was lower than that explained by QTLs involved in epistatic interactions.CONCLUSION: The findings showed that most main effect QTLs for AACs detected tended to be co-localised within the genome. Thus, if a breeder were interested in changing the concentration of only one amino acid, this might be difficult to achieve. Meanwhile, the prevalent epistasis for the loci involved appeared to hold true for the content of amino acids. The information reported in the present study is expected to be useful for future breeding programmes targeting the development of improved rice amino acid composition for human nutrition.